Predicting post-traumatic growth based on spiritual and social well-being in women affected by extramarital relationships - Anvarian, Ehtera Sadat; Ahmadi, Atefeh; Babaei, Arezo; Nazeriyeh, Atefeh (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The purpose of the present study was to predict post-traumatic growth based on spiritual and social well-being in women affected by extramarital relationships. Method: The current research method was descriptive-correlation type. The research population included all women who referred to Shahriar health assessment centers, of which 282 women who met the criteria for entering the research were selected by purposive sampling; Then they were evaluated by Tedeschi and Calhoun (1996) post-traumatic growth questionnaire, Palotzin and Ellison (1982) spiritual well-being questionnaire, and Keyes (1998) social well-being questionnaire. Pearson's correlation coefficient and regression analysis were used to analyze the data. Results: The results showed that spiritual well-being and social well-being significantly predict post-traumatic growth in women (p